The effect of shadow economy on foreign direct investment: Empirical evidence in emerging market economies 1988-2018 - Martakusuma, Aghni Majida; Widodo, Wahyu (Asian Journal of Economic Modelling, 2024)
This paper aims to examine the effect of shadow economy on foreign direct investment (FDI) in emerging market economies (EMEs) starting from 1988 to 2018. The error-correction model (ECM) is applied to estimate the dynamic panel data in the short run model, and for the long run model, this study applied ordinary panel data approach to both the fixed effect model (FEM) and the random effect model (REM). This study considers the global financial crisis of 1998 by dividing the estimation into three periods, i.e., pre-crisis, post-crisis, and all periods. The results show that shadow economy had a significantly negative effect on FDI inward both in the long run and the short run during the pre-crisis period, while economic growth, trade openness, policy rate, population, and infrastructure had various significant effects on FDI inward. The long-run estimation revealed that economic growth, policy rate, inflation, and the human development index (HDI) were all significant factors. Only the exchange rate, as one of efficiency-seeking motives and macroeconomic factors, has a significant role in FDI in EMEs. This analysis suggests that policymakers need to consider shadow economy along with investor motives and macroeconomic variables to provide more FDI, while investors need to consider the country’s advantages that could potentially provide a rate on return on investment.